2013
DOI: 10.3390/coatings3020082
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Methacrylic Acid (EMAA) Single Splat Morphology

Abstract: Abstract:A single splat is the building block of a thermal spray coating; thus, investigating single splats is essential to understanding thermal spray coatings and their properties. In this study, the morphology of flame sprayed ethylene methacrylic acid (EMAA) splats, deposited at various stand-off distances (SODs) onto glass and mild steel substrates were investigated using a scanning electron microscope, Leica M Stereo-microscope, the WYKO surface profiler and the ContourGT surface profiler. This work anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…The higher surface roughness results in a higher surface wettability. 182 184 The sol–gel Nb 2 O 5 -coated implants have more hydrophilic surface than bare ones irrespective of the chemical composition of the implant and the medium used for contact angle measurement. 105 , 126 …”
Section: Pure Nb X O Y ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The higher surface roughness results in a higher surface wettability. 182 184 The sol–gel Nb 2 O 5 -coated implants have more hydrophilic surface than bare ones irrespective of the chemical composition of the implant and the medium used for contact angle measurement. 105 , 126 …”
Section: Pure Nb X O Y ...mentioning
confidence: 99%
“…At higher values of hydrophilicity, i.e., at lower contact angles, the number of adsorbed proteins over the surface of the implant is increased, leading to superior cell adhesion and improved implant/cell interaction. The higher surface roughness results in a higher surface wettability. The sol–gel Nb 2 O 5 -coated implants have more hydrophilic surface than bare ones irrespective of the chemical composition of the implant and the medium used for contact angle measurement. , …”
Section: Pure Nb X O Y Coatingsmentioning
confidence: 99%
“…In general, increasing SOD to 35 cm results in the formation of disk-shaped splats. A higher percentage of the splash morphology was observed on mild steel substrates than glass substrates (Ref 23,26,27). It is suggested that more rapid freezing occurs on mild steel than on glass substrates due to the higher thermal conductivity of the steel (Ref 28).…”
Section: Influence Of Spray Distance On Splatmentioning
confidence: 99%